The winged lion and the eight-pointed cross - Mallia-Milanes, Victor, 1940- author.
1 online resource.
Keywords: "The papers reprinted in this volume focus on the extraordinary and multifaceted relationship between two Christian States: the Republic of Venice and the Island Order State on Hospitaller Malta between 1530 and the late 1790s. It was marked by three distinct phenomena - military cooperation along with other western allies against the Ottoman Empire, direct mutual confrontation, at times even leading to war, and commercial cooperation. A fourth phenomenon, this time involving the wider Mediterranean context within which the two interacted, concerns the idea of decline. Some of the papers that follow question the validity of the traditional view that the Mediterranean and Venice were in decline by the sixteenth century, and that the Hospitaller Order, claimed to be in decline by the eighteenth, had given up Malta to the French as a result. This book will appeal to all those interested in Crusading Orders, the History of the Crusades, as well as the History of Venice, Malta, and the Mediterranean in the Early Modern Age"--